1124. Effects of Co-infection on the Severity, Response to Treatment and Duration of Hospital Stay in Patients with Clostridium difficile Infection. (26th November 2018) - Shafiq, Muhammad; Alturkmani, Hani; Zafar, Yousaf; Mittal, Vishal; Lodhi, Hafsa; Brewer, Joseph
Abstract: Background: According to the multicenter evaluation of the FilmArray ® multiplex gastrointestinal (GI) panel for etiologic diagnosis of infectious gastroenteritis, the GI panel detected at least one potential pathogen in 53.5% of the stool specimens that were collected. Out of the positive samples, 31.5% tested positive for more than one potential pathogen. The samples that were co-infected showed that Clostridium difficile infection (CDI) was present in 53.4% of them. This lead to the idea of our project to determine whether the presence of another GI infection affects CDI outcomes in terms of severity, treatment escalation, duration of hospital stay and recurrence. Methods: Inclusion criteria: 18-year-old and above patients. Exclusion criteria are GI panel performed on outpatient basis, presence of any co-founder that had independent effect on the outcomes such as end-stage renal disease, cirrhosis, presence of non-GI infection (pneumonia, urinary tract infection, osteomyelitis etc.), and recurrent CDI. Out of the 2, 576 GI panels performed from January 1, 2015 until December 31, 2016; only 235 patients were selected for retrospective chart review based on the above criteria. Out of 235 patients, 38 patients had co-infection (CDI + another GI infection = Group A) and reminder had only CDI (Group B). Chi-square test, Fisher's exact test (for severity, treatment escalation and recurrence) and Independent T-test (for duration of hospital stay) were used to compare Group A with Group B. Alpha criterion was 0.05. Results: The P -values for each outcome are given below: (a) 0.16 for severity according to definition of American College of Gastroenterology. (b) 0.77 for severity according to definition of Infectious Disease Society of America. (c) 0.23 for treatment escalation. (d) 0.41 for duration of hospital stay. (e) 0.49 for CDI recurrence. Conclusion: All the resulted P -values are greater than 0.05. These results are suggestive of the fact that presence of another GI infection does not affect the outcomes for CDI in terms of severity, treatment escalation, duration of hospital stay, and recurrence. As there were only 38 patients in co-infection group, it limits the ability to determine the effect of individual infectious agent on the outcomes of CDI. Disclosures: All authors: No reported disclosures.